Infant and Child MRI: A Review of Scanning Procedures - Copeland, Anni; Silver, Eero; Korja, Riikka; Lehtola, Satu J.; Merisaari, Harri; Saukko, Ekaterina; Sinisalo, Susanne; Saunavaara, Jani; Lähdesmäki, Tuire; Parkkola, Riitta; Nolvi, Saara; Karlsson, Linnea; et al. (Frontiers in Neuroscience, 2021)
Magnetic resonance imaging (MRI) is a safe method to examine human brain. However, a typical MR scan is very sensitive to motion, and it requires the subject to lie still during the acquisition, which is a major challenge for pediatric scans. Consequently, in a clinical setting, sedation or general anesthesia is often used. In the research setting including healthy subjects anesthetics are not recommended for ethical reasons and potential longer-term harm. Here we review the methods used to prepare a child for an MRI scan, but also on the techniques and tools used during the scanning to enable a successful scan. Additionally, we critically evaluate how studies have reported the scanning procedure and success of scanning. We searched articles based on special subject headings from PubMed and identified 86 studies using brain MRI in healthy subjects between 0 to 6 years of age. Scan preparations expectedly depended on subject’s age; infants and young children were scanned asleep after feeding and swaddling and older children were scanned awake. Comparing the efficiency of different procedures was difficult because of the heterogeneous reporting of the used methods and the success rates. Based on this review, we recommend more detailed reporting of scanning procedure to help find out which are the factors affecting the success of scanning. In the long term, this could help the research field to get high quality data, but also the clinical field to reduce the use of anesthetics. Finally, we introduce the protocol used in scanning two to five-week-old infants in the FinnBrain Birth Cohort Study, and tips for calming neonates during the scans.